Burden of rare variants in causative genes for amyotrophic lateral sclerosis (ALS) accelerates age at onset of ALS. Issue 5 (24th October 2018) - Naruse, Hiroya; Ishiura, Hiroyuki; Mitsui, Jun; Takahashi, Yuji; Matsukawa, Takashi; Tanaka, Masaki; Doi, Koichiro; Yoshimura, Jun; Morishita, Shinichi; Goto, Jun; Toda, Tatsushi; Tsuji, Shoji
Abstract : Objectives: To evaluate the burden of rare variants in the causative genes for amyotrophic lateral sclerosis (ALS) on the age at onset of ALS in a Japanese case series. Methods: We conducted whole-exome sequencing analysis of 89 families with familial ALS (FALS) and 410 patients with sporadic ALS (SALS) to identify known pathogenic mutations or rare functionally predicted deleterious variants in the causative genes for ALS. Rare variants (minor allele frequency <1%) with scaled Combined Annotation-Dependent Depletion score >20 were defined as rare functionally predicted deleterious variants. The patients with ALS were classified on the basis of the number of pathogenic and/or rare functionally predicted deleterious variants, and the age at onset was compared among the classified groups. Results: Whole-exome sequencing analysis revealed known pathogenic mutations or rare functionally predicted deleterious variants in causative genes for ALS in 56 families with FALS (62.9%) and 87 patients with SALS (21.2%). Such variants in multiple genes were identified in seven probands with FALS and eight patients with SALS. The ages at onset in the patients with ALS with multiple variants were significantly earlier than those in other patients with ALS. Even when the patients with known pathogenic mutations were excluded, a significantly earlier onset of the disease was still observed in patients with multiple rare functionally predicted deleterious variants. Conclusions: A substantial number of patients carried rare variants in multiple genes, and the burden of rare variants in the known causative genes for ALS affects the age at onset in the Japanese ALS series.